Effect Observation of Electro-Acupuncture Anesthesia Combined with General Anesthesia in Elderly Patients Undergoing Gastrointestinal Tumor Resection - Xu, Jiping; Li, Peng; Zheng, Liyan; Chen, Qiong (Frontiers in Surgery, 2022)
Objective. To investigate the anesthetic effect of acupuncture anesthesia combined with general anesthesia in elderly patients undergoing gastrointestinal tumor resection, and to analyze the effects of acupuncture anesthesia on inflammatory factors, stress state and T lymphocyte subsets in elderly patients. Methods. Total of 118 elderly patients who underwent gastrointestinal tumor resection in our hospital from June 2018 to March 2021 were selected and divided into the control group (59 cases) and the observation group (59 cases) according to the random number method. General anesthesia was adopted in the control group and acupuncture anesthesia combined with general anesthesia was adopted in the observation group. The anesthesia effect, stress state, levels of inflammatory factors, T-lymphocyte subsets and adverse reactions were compared. Results. The VAS score, agitation score and respiratory normalization time in the observation group were lower than those in the control group (P<0.05). After surgery, the levels of serum Cor, ET, NE and DA in the observation group were lower than those in the control group (P<0.05). At 24h after surgery, the levels of serum TNF-α, IL-6 and IL-1β in the observation group were lower than those in the control group (P<0.05). At 24h after surgery, the levels of CD3+, CD4+, and CD4+/CD8+ in the two groups were lower than those before surgery, and the levels of CD3+, CD4+, and CD4+/CD8+ in the observation group were higher than those in the control group (P<0.05). During the hospitalization, the total incidence rate ofadverse reactions after anesthesia in the observation group was lower than that in the control group (P<0.05). Conclusion. Acupuncture anesthesia combined with general anesthesia has good anesthesia effect when used for gastrointestinal tumor resection in the elderly. It can stabilize the internal environment of patients, alleviate postoperative stress response and inflammatory response, and regulate the body immune function. Moreover, it has high safety and can significantly reduce the occurrence of postoperative adverse reactions.